Japan's productivity and GDP growth: The role of private, public and foreign R&D 1967-2017 - Thomas Ziesemer (Economies, 2020)
We analyze the dynamic interaction of Japan's total factor productivity, gross domestic product (GDP) domestic and foreign private and public research and development (R&D) in vector-error-correction models (VECMs) for Japan with data from 1963-2017. Extensive testing leads to favoring a model with five cointegrating equations for the six variables. Analysis of effects of permanent policy changes shows that (i) additional public R&D encourages private R&D and total factor productivity (TFP), and has higher internal rates of return than private R&D changes and therefore could speed up Japan's growth; (ii) public R&D changes have a statistically significant positive permanent effect on foreign private R&D stocks and a transitional effect on foreign public R&D stocks; (iii) private R&D changes have a statistically significant positive permanent effect on foreign public R&D stocks and a transitional effect on foreign private R&D stocks; (iv) after a temporary GDP change, public R&D is counter-cyclical in the short and medium run and private R&D is pro-cyclical. Empirical results are related to the parameters of a VES (variable elasticity of substitution) function for TFP production.
Keywords: F43; O19; O47; O53; 330; public and private R&D; productivity; growth; spillovers; vector-auto-regression/error-correction (VAR/VECM)